Bioserotypes, Virulence Markers, and Antimicrobial Susceptibility of Yersinia enterocolitica Strains Isolated from Free-Living Birds. (17th March 2020) - Odyniec, Marta; Stenzel, Tomasz; Ławreszuk, Dorota; Bancerz-Kisiel, Agata
Abstract : The risk of meat contamination with Yersinia enterocolitica poses a threat to consumers and persons who come into contact with bird carcasses. The occurrence of Y . enterocolitica in the vast majority of migratory game species, the capercaillie, and the black grouse has never been studied in Poland, Europe, or in the world. The material for the study consisted of cloacal swabs obtained from 143 Eurasian coots, 50 mallards, 30 pochards, 27 greylag geese, 22 white-fronted geese, 22 bean geese, 20 green-winged teals, and 10 tufted ducks, as well as fecal swabs obtained from 105 capercaillie and 18 black grouse. Bacteriological examinations of 894 samples taken from 447 birds led to the isolation of 20 strains with the biochemical features characteristic of the genus Yersinia . All 20 strains were molecularly examined, and the genes characteristic of Y . enterocolitica were detected in 8 strains. The isolated strains harbored amplicons whose size corresponded to ystB gene fragments. Four strains belonged to bioserotype 1A/NI, one strain was identified as bioserotype 1B/O:9, and one as 1A/O:9. The prevalence of Y . enterocolitica was determined at 1.4% in green-winged teals, at 5.0% in Eurasian coots, and at 4.8% in capercaillie. All strains were resistant to amoxicillin with clavulanic acid, ampicillin, and cefalexin. The strains isolated from migratory birds were also resistant to kanamycin and streptomycin, and they were characterized by resistance or intermediate resistance to cefotaxime, ceftazidime, chloramphenicol, gentamycin, and tetracycline, to which the strains isolated from the capercaillie were susceptible. Yersinia enterocolitica was not detected in the remaining bird species. The presence of Y . enterocolitica in green-winged teals, Eurasian coots, and capercaillie indicates that these birds could be carriers, potential reservoirs, and sources of infection for humans. They can also be regarded as reliable bioindicators of Y . enterocolitica in their respective habitats.